Use of a standardized code status explanation by residents among hospitalized patients - Kriti Mittal; Kapil Sharma; Neha Dangayach; Dhaval Raval; Katherine Leung; Susan George; George Abraham (Greater Baltimore Medical Center, 2014)
Objectives: There is wide variability in the discussion of code status by residents among hospitalized patients. The primary objective of this study was to determine the effect of a scripted code status explanation on patient understanding of choices pertaining to code status and end-of-life care. Methods: This was a single center, randomized trial in a teaching hospital. Patients were randomized to a control (questionnaire alone) or intervention arm (standardized explanation+ questionnaire). A composite score was generated based on patient responses to assess comprehension. Results: The composite score was 5.27 in the intervention compared to 4.93 in the control arm (p=0.066). The score was lower in older patients (p<0.001), patients with multiple comorbidities (p≤0.001), KATZ score <6 (p=0.008), and those living in an assisted living/nursing home (p=0.005). There were significant differences in patient understanding of the ability to receive chest compressions, intravenous fluids, and tube feeds by code status. Conclusion: The scripted code status explanation did not significantly impact the composite score. Age, comorbidities, performance status, and type of residence demonstrated a significant association with patient understanding of code status choices. Practice implications: Standardized discussion of code status and training in communication of end-of-life care merit further research.